Technical manual for high-quality and low-emission rice production in the Mekong River Delta - National Agriculture Extension Center (2025)
The 2025 guideline was revised to be more workable across the Mekong Delta’s varied conditions (considering infrastructure, mechanization, seasons, low-lying areas, and rice varieties). For water management, drainage is made more flexible: at least two drainage periods from tillering to before heading, with fields kept dry for at least three continuous days each time; in low-lying zones or very rainy seasons, one drainage period may be used while still meeting emissions-reduction goals. For seeding and fertilization, it adds a clear seed-rate roadmap (≤80 kg/ha before 2028; ≤70 kg/ha from 2028) and, introduces the benefits of applying seeding combined with fertilizer incorporation, which are reduced nitrogen rate by 10–15% and shifts to two fertilizer applications instead of three. For straw management, it prioritizes collecting straw for reuse; if collection isn’t possible, it is recommended to incorporate straw with bioproducts under non-flooded conditions. It also adds post-harvest drying/storage technologies and encourages digital monitoring to cut losses and improve grain quality.